2020
DOI: 10.1111/nph.16839
|View full text |Cite
|
Sign up to set email alerts
|

Beyond flowering time: diverse roles of an APETALA2‐like transcription factor in shoot architecture and perennial traits

Abstract: Polycarpic perennials maintain vegetative growth after flowering. PERPETUAL FLOWERING 1 (PEP1), the orthologue of FLOWERING LOCUS C (FLC) in Arabis alpina regulates flowering and contributes to polycarpy in a vernalisation-dependent pathway. pep1 mutants do not require vernalisation to flower and have reduced return to vegetative growth as all of their axillary branches become reproductive. To identify additional genes that regulate flowering and contribute to perennial traits we performed an enhancer screen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…The molecular mechanisms regulating juvenile-adult phase change in A. alpina are similar to those described in Arabidopsis thaliana, where this trait is regulated by the sequential action of two microRNAs, miR156 and miR172 (Wu et al, 2009). Typically, miR156 accumulates in the apices of young seedlings and decreases as plants become older and reach reproductive maturity, while at the same time levels of miR172 increase (Wu et al, 2009) (AaTOE2; Bergonzi et al, 2013;Hyun et al, 2019;Lazaro et al, 2019;Zhou et al, 2021). While the role of these genes in the age pathway is conserved between Arabidopsis thaliana and A. alpina, they additionally contribute to polycarpy of A. alpina (Table 1).…”
Section: Juvenile Phasementioning
confidence: 89%
See 1 more Smart Citation
“…The molecular mechanisms regulating juvenile-adult phase change in A. alpina are similar to those described in Arabidopsis thaliana, where this trait is regulated by the sequential action of two microRNAs, miR156 and miR172 (Wu et al, 2009). Typically, miR156 accumulates in the apices of young seedlings and decreases as plants become older and reach reproductive maturity, while at the same time levels of miR172 increase (Wu et al, 2009) (AaTOE2; Bergonzi et al, 2013;Hyun et al, 2019;Lazaro et al, 2019;Zhou et al, 2021). While the role of these genes in the age pathway is conserved between Arabidopsis thaliana and A. alpina, they additionally contribute to polycarpy of A. alpina (Table 1).…”
Section: Juvenile Phasementioning
confidence: 89%
“…Orthologues of some of these genes have been functionally characterized in A. alpina and it has been demonstrated that they equally contribute to the age-dependent control of flowering. These factors include the A. alpina orthologues of SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE15 (AaSPL15), PERPETUAL FLOWERING2 (PEP2, the A. alpina orthologue of AP2) and TARGET OF EAT2 (AaTOE2; Bergonzi et al, 2013;Hyun et al, 2019;Lazaro et al, 2019;Zhou et al, 2021). While the role of these genes in the age pathway is conserved between Arabidopsis thaliana and A. alpina, they additionally contribute to polycarpy of A. alpina (Table 1).…”
Section: Juvenile Phasementioning
confidence: 99%
“…Orthologs of some of these genes have also been functionally characterised in A. alpina and it has been demonstrated that they contribute to the age-dependent control of flowering. These factors include the A. alpina orthologs of SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE15 (AaSPL15 ), PERPETUAL FLOWERING2 (PEP2 , the A. alpina ortholog of AP2 ) and TARGET OF EAT2 (AaTOE2 ; Bergonzi et al, 2013;Hyun et al, 2019;Lazaro et al, 2019;Zhou, Gan, Viñegra de la Torre, Neumann, & Albani, 2021).…”
Section: Juvenile Phase Lengthmentioning
confidence: 99%
“…thaliana and A. alpina , they additionally contribute to the polycarpy of A. alpina, which maintains vegetative growth after flowering (Table 1). For example, polycarpy is compromised inpep2 and toe2 mutants, and in transgenic lines that express microRNA resistant forms of AaSPL15, in which all axillary branches become reproductive (Table 1; Hyun et al, 2019;Lazaro et al, 2019;Zhou et al, 2021). These additional roles of age-related factors in polycarpic A. alpina may result from a more prominent role of the age-pathway than in A. thaliana, in which the age-pathway cannot be bypassed by other flowering-time pathways (Hyun, Richter, & Coupland, 2017;Hyun et al, 2019).…”
Section: Juvenile Phase Lengthmentioning
confidence: 99%
“…We used a forward genetic approach to define different functional steps during root hair development in A. alpina. Two EMS screens were performed in independent populations: one in Pajares (Wang et al, 2009), representing 4,205 M1 plants, and the other in the pep1-1 background (Wang et al, 2009;Albani et al, 2012;Bergonzi et al, 2013;Zhou et al, 2021), representing 6,800 M1 individuals. Seeds of five M1 plants were pooled, and 50 M2 seedlings from each pool were screened for root hair phenotypes.…”
Section: Isolation Of Root Hair Mutants In a Alpinamentioning
confidence: 99%